Post-Translational Modifications of Exosomal Proteins - Moreno-Gonzalo, Olga; Villarroya-Beltri, Carolina; Sánchez-Madrid, Francisco (Frontiers in Immunology, 2014)
Exosomes mediate intercellular communication and participate in many cell processes such as cancer progression, immune activation or evasion, and the spread of infection. Exosomes are small vesicles secreted to the extracellular environment through the release of intraluminal vesicles contained in multivesicular bodies (MVBs) upon the fusion of these MVBs with the plasma membrane. The composition of exosomes is not random, suggesting that the incorporation of cargo into them is a regulated process. However, the mechanisms that control the sorting of protein cargo into exosomes are currently elusive. Here we review the post-translational modifications detected in exosomal proteins, and discuss their possible role in their specific sorting into exosomes.